POST-TREATMENT FOLLOW-UP OF NASOPHARYNGEAL CARCINOMA PATIENTS: A REVIEW - Ika Dewi Mayangsari (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2019)
Introduction Locoregional failure of nasopharyngeal carcinoma (NPC) occurs despite the aggressive treatment that has been done. Optimal and accurate follow-up schedule after the radiotherapy or chemoradiotherapy sessions could improve the patient's quality of life (QoL). Discussion Kwong et al. reported complete histological remission within 3 months after therapy and positive histological signs at >12 weeks considered a persistent disease. Kong et al. (2017) showed that the pathological treatment response using CT scan and MRI and stated that the median time to full regressions is 4.9 months. Some studies also reported that primary tumor continuously regressed >4 months after treatment and delayed remission >12 weeks is not a prognostic factor for poor survival. The use of MRI is superior to CT scan to detect residual or recurrent NPC. MRI showed good results in differentiating mature scar and tumor, whereas CT scan could not differentiate fibrosis and tumor because of the radiation therapy-induced inflammation. On the other hand, PET-CT has higher sensitivity compared to CT scan and MRI, but poor cost-effectiveness. Various studies and NCCN 2018 guidelines recommend the use of imaging between the third and sixth months after therapy to evaluate treatment response. Conclusion Assessment of treatment-related late toxicities also an important factor to improve patient’s QoL. Evaluation of nutrition, speech difficulties, swallowing, hearing, dental care should be done annually and peer support groups can help improve patient’s QoL. Assessment of residual disease should be done at the minimum of 10 weeks after the completion of the therapy and long-term follow-up is a must because locoregional recurrences of NPC are common within the first two to three years after the treatment.